Quality of Life in Postoperative Colorectal Cancer Survivors: A Structural Equation Model - Suttipong, Chophaka; Sindhu, Siriorn; Utriyaprasit, Ketsarin; Iramaneerat, Cherdsak (Siriraj Medical Journal, 2021)
Objective: The present study has been aimed at constructing a causal model to determine factors affecting healthrelated quality of life (HRQoL) in postoperative patients with colorectal cancer (CRC) following discharge. Materials and Methods: A cross-sectional study was conducted with 396 postoperative CRC cancer patients from ten tertiary hospitals representing each of the four Regions of Thailand. Data was collected through a standard questionnaire. Structure equation modeling (SEM) was applied to analyze data. Results: The findings revealed that the majority of patients with CRC surgery had a moderate HRQoL. One hundred and twenty-three patients (31.1%) had complications. SEM showed a good fit with ƛ2=40.347, df=28, p=0.062, GFI=0.980, CFI=0.959 and RMSEA=0.033. The final model showed that age, stage of cancer and healthcare service being received following CRC surgery had direct effects on HRQoL. Nutritional status and follow-up outpatient clinic had indirect effects on HRQoL during postoperative complications. Moreover, social support and primary family caregiver support had indirect effects on HRQoL through self-management capacity. Conclusion: The findings of this study emphasized the importance of implementing effective strategies to improve quality of life among postoperative patients with CRC after discharge and indicated these strategies should focus on quality of healthcare service following CRC surgery, self-management capacity and prevention of postoperative complications. Postoperative complications can be reduced by providing effective follow-up in outpatient clinics and nutritional status management, consequently improving quality of life among this population.